(untitled) (Journal of Environmental Science and Natural Resources, 2022)
The study was conducted to explore the physicochemical parameters of surface water from the construction work involving the bridge over the river Kohelia and road along the bank of Kohelia for the construction of access road for Matarbari Coal Fired Power Plant is under construction area of Bangladesh starting from September 2020 to September 2021. The surface water samples were collected from three sampling stations in the Kohelia for the construction of access road for Matarbari. The result of the study showed that pH, Temperature (T), Dissolved Oxygen (DO), Total Suspended Solids (TSS), Turbidity, Electric Conductivity (EC), Total Dissolved Solids (TDS), Total Coliform (TC) and Fecal Coliform (FC) were ranged from 6.6 to 8.2, 24.8 to 31.6ºC, 4.3 to 6.1 mg/L, 4.0 to 15.0 mg/L, 7.4 to 117.0 NTU, 24.3 to 725.0 μS/cm, 200.0 to 2721.0 mg/L, 23.6 to 644.0 N/100 ML and 11.0 to 312.0 N/100 ML respectively. Some parameters showed no significant change with the time period. This might happen due to periodic changes per day or month due to tidal effects as the study area of Kohelia River is very close estuary of the Bay of Bengal. Except pH and Temperature (T), all others physicochemical parameters were across the acceptable range of standard limits. The Comparative study showed Total and Fecal coliform is higher than the Standard might be happen due to piling slurry, concrete debris, wastewater, unhygienic sanitary waste, soil & silt dumping, surface runoff, oil and grease littering, solid waste created by workers, encroachment etc. Environ. Sci. & Natural Resources, 13(1&2): 76-81, 2020